Thai nurse cohort study: cohort profiles and key findings. Issue 1 (December 2016) - Sawaengdee, Krisada; Tangcharoensathien, Viroj; Theerawit, Tuangtip; Thungjaroenkul, Petsunee; Thinkhamrop, Wilaiphorn; Prathumkam, Panuwat; Chaichaya, Nathaphop; Thinkhamrop, Kavin; Tawarungruang, Chaiwat; Thinkhamrop, Bandit
Abstract Background Globally, the nursing profession faces shortages, high turnover, and inequitable distribution. These problems are particularly acute in South East Asia. The present paper describes the design and initial findings of the Thai Nurse Cohort Study (TNCS). Methods The TNCS is a longitudinal prospective cohort study comprising multiple age cohorts, initiated in 2009 and expected to run until 2027. Cohorts comprise registered nurses (RN) holding professional licenses granted by the Thailand Nursing and Midwifery Council. Follow-up is at 3-year intervals, with new (younger) TNCS cohorts introduced and older, no-longer eligible members checked out. This maintains the cohort size as representative of the Thai RN population. The first survey round (2009) used a self-administered mailed questionnaire. The second round (2012) provided follow-up of the initial cohort and formed the baseline survey of new entries. Results The sampling frame for the first round was 142, 699 licensed RN; 50, 200 age-stratified participants were randomly selected and mailed the questionnaire, and 18, 198 questionnaires were returned owing to incorrect addresses. Of the remaining 32, 002 participants, 18, 756 (58.6 %) responded (average age 43.7 ± 9.8 years). About 15.4 % (equivalent to 20, 000 of the current RN population), reported an intention to leave their nursing career. The second round achieved a follow-up rate of 60.2 %. This round included 3020 participants randomly selected from 6402 new RN (response rate, 38.3 %; mean age 23.1 ± 3.5 years). In this round, 11.2 % reported they intended to leave nursing in the next 2 years. Conclusions These two survey rounds have highlighted that Thailand is facing critical nurse shortages. A high rate of nurses expressed an intention to leave the profession; the capacity to replace these potential losses is much lower.